2008
DOI: 10.5132/jbse.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Viability of the Use of the Sand Dollar Mellita quinquiesperforata as a Test Organism

Abstract: RESUMOEste estudo teve por objetivo investigar a viabilidade do uso da bolacha-do-mar Mellita quinquiesperforata como organismoteste em experimentos crônicos de curta duração. Para isto foi aplicado o protocolo da Norma Técnica da CETESB destinada ao ouriço regular Lytechinus variegatus, utilizando embriões e larvas expostos a quatro tóxicos de referência por um período de 24 horas. As substâncias utilizadas foram sulfato de zinco, dicromato de potássio, sulfato de cobre e dodecil sulfato de sódio (DSS). Essas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…Despite the low number of tests carried out on species of echinodermatas other than L. variegatus, the values obtained are within the range of variation and/or of the same order of magnitude observed by other authors who investigated the sensitivity of A. lixula LAITANO, 2002;MÁXIMO et al, 2008;RESGALLA et al, 2012), E. lucunter (RUMBOLD; SNEDAKER, 1997; RESGALLA JÚNIOR; LAITANO, 2002) and the sand dollar Mellita quinquiesperforata (LAITANO et al, 2008), which validate the results obtained in this work. On the basis of this, it was suggested that the different species tested have similar sensitivity, or order of sensitivity to the different metals tested, whether essential or non-essential.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Despite the low number of tests carried out on species of echinodermatas other than L. variegatus, the values obtained are within the range of variation and/or of the same order of magnitude observed by other authors who investigated the sensitivity of A. lixula LAITANO, 2002;MÁXIMO et al, 2008;RESGALLA et al, 2012), E. lucunter (RUMBOLD; SNEDAKER, 1997; RESGALLA JÚNIOR; LAITANO, 2002) and the sand dollar Mellita quinquiesperforata (LAITANO et al, 2008), which validate the results obtained in this work. On the basis of this, it was suggested that the different species tested have similar sensitivity, or order of sensitivity to the different metals tested, whether essential or non-essential.…”
Section: Discussionsupporting
confidence: 69%
“…This downward trend of differences in sensitivity in Echinodermata has already been highlighted by other studies in Brazil involving different test organisms (RESGALLA JÚNIOR; LAITANO, 2002;MÁXIMO et al, 2008;LAITANO et al, 2008). Associated with this, HIS et al (1999), in studies on tests with molluscs, also emphasize that species with distinct ecological and phylogenetic characteristics may respond similarly to some toxicants.…”
Section: Discussionmentioning
confidence: 68%
“…Nitokra sp showed more sensitivity to potassium dichromate compared to freshwater fish such as Piracactus mesopotamicus (pacu); Hyphessobrycon eques (weed-thick) and Phalloceros. caudimaculttus (guarú) (Cruz et al, 2008), and less sensitivity than embryos of echinoids such as Mellita quinquesperforata, Arbacia lixula and Lytechinus variegatus, frequently used in aquatic tests in studies developed by Resgalla & Laitano (2002); Laitano et al (2008) and Maximo et al (2008), respectively (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Já os ensaios de toxicidade crônica são realizados com ouriços-do-mar coletados diretamente do ambiente e, portanto, restrito aos locais onde há a presença destas espécies (ABNT, 2006b). Devido à limitação regional com que as espécies normalizadas são encontradas no ambiente, ensaios crônicos utilizando organismos alternativos têm sido testados (Laitano et al, 2008;Jorge & Moreira, 2005). No entanto, nem todos apresentam os critérios necessários para serem utilizados rotineiramente como organismo-teste, tais como: curto ciclo de vida, facilidade de cultivo e/ou representatividade ecológica.…”
Section: Introductionunclassified